Lobetyolin Suppressed Osteoclastogenesis and Alleviated Bone Loss in Ovariectomy-Induced Osteoporosis via Hindering p50/p65 Nuclear Translocation and Downstream NFATc1/c-Fos Expression - Xiu C; Luo H; Huang W; Fan S; Yuan C; Chen J; Xu C; Yao C; Hong D; Zhang L (Drug Design, Development and Therapy)
Chunmei Xiu,1,2,* Hua Luo,3,* Weixing Huang,4,5,* Shaohua Fan,3 Chiting Yuan,3 Jiangjie Chen,3 Chenghao Xu,3 Can Yao,3 Dun Hong,1,3 Liwei Zhang1,3 1Institute of Bone Metabolism, Taizhou Hospital of Zhejiang Province, School of Medicine, Zhejiang University, Taizhou, 317000, People’s Republic of China; 2Department of Clinical Medicine, Key Laboratory of Novel Targets and Drug Study for Neural Repair of Zhejiang Province, School of Medicine, Hangzhou City University, Hangzhou, 310015, People’s Republic of China; 3Orthopedic Department, Taizhou Hospital of Zhejiang Province, School of Medicine, Zhejiang University, Taizhou, 317000, People’s Republic of China; 4General Surgical Department, Taizhou Hospital of Zhejiang Province, School of Medicine, Zhejiang University, Taizhou, 317000, People’s Republic of China; 5Department of Nursing, Zhejiang University School of Medicine First Affiliated Hospital, School of Medicine, Zhejiang University, Hangzhou, 310000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Liwei Zhang, Email medzlw@sina.com Dun Hong, Email hongd@enzemed.comPurpose: To investigate the therapeutic potential of lobetyolin (LBT), a bioactive compound derived from Codonopsis pilosula, against bone loss in postmenopausal osteoporosis (PMOP).Methods: To investigate the therapeutic potential of LBT in osteoporosis, a multifaceted approach involving network pharmacology and molecular docking was employed to identify relevant targets and elucidate mechanisms of action. In vitro experiments evaluated LBT’s impact on osteoclastogenesis, bone resorption, and osteoblast differentiation using bone marrow macrophages (BMMs) and bone marrow mesenchymal stromal cells (BMSCs). The inhibition of RANKL-activated NF-κB signaling and downstream NFATc1/c-Fos pathways was analyzed via Western blot and immunofluorescence. Additionally, an in vivo ovariectomy (OVX)-induced osteoporosis mouse model was utilized to examine the effects of LBT on bone architecture, assessed through micro-CT imaging and histological analyses.Results: LBT effectively suppressed RANKL-driven osteoclast differentiation in vitro without cytotoxic effects, reducing osteoclast numbers, size, and resorptive function. It also downregulated osteoclast-specific genes expressions, inhibited ROS production, and disrupted the NF-κB signaling cascade by blocking p50/p65 nuclear translocation. Moreover, LBT mitigated LPS-induced osteogenic impairment, enhancing osteoblast differentiation and mineralization. In the OVX mouse model, LBT treatment improved bone microstructure. Histological analyses further corroborated LBT’s role in reducing osteoclast activity and promoting bone formation.Conclusion: LBT exerts a dual effect on bone remodeling, simultaneously inhibiting osteoclast-mediated bone resorption and promoting osteoblast-driven bone formation. By targeting key pathways such as NF-κB/NFATc1/c-Fos and reducing inflammatory responses, LBT emerges as a potential therapeutic agent for managing PMOP and other conditions associated with excessive bone loss, offering a safer alternative to current treatments. Keywords: postmenopausal osteoporosis, osteoclast, lobetyolin, inflammation, osteoblast